„Polska Bibliografia Bibliologiczna” jako źródło do dziejów książki i biblioteki jasnogórskiej - Bajor, Agnieszka (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The paper focuses on the bibliography concerning the issue of the books and the library in the Jasna Góra Monastery. The author used fifty-eight texts (books, magazine articles and publications included in part-works), which were found in The Polish Bibliography of Bibliology in printed (1937-2007) and electronic (1995-) versions. The material was divided into four thematic groups: The library of the Jasna Góra Monastery, Library Collections in Jasna Góra in Częstochowa, Manuscripts and archive material in Jasna Góra, Printing industry in Jasna Góra. The work also presents the research problems already discussed by the researchers, such as the history of the library in 17th and 18th centuries (Fr. Leander Pietras, Fr. Jarosław Łuniewski), the iconographic program of the library interior (Anna Stępnik, Mariusz Karpowicz), the protection of the collections (Leonard Ogierman), the history of the Pauline copyists and their works (Fr. Janusz Zbudniewek) and the history of the printing house of Jasna Góra and its products (Henryk Czerwień). The existing studies should be regarded as rich but still insufficient.